Early results of lower dose dasatinib (50 mg daily) as frontline therapy for newly diagnosed chronic‐phase chronic myeloid leukemia. Issue 13 (3rd May 2018) - Naqvi, Kiran; Jabbour, Elias; Skinner, Jeffrey; Yilmaz, Musa; Ferrajoli, Alessandra; Bose, Prithviraj; Thompson, Philip; Alvarado, Yesid; Jain, Nitin; Takahashi, Koichi; Burger, Jan; Estrov, Zeev; et al.
Abstract : BACKGROUND: Dasatinib is a potent BCR‐ABL1 and Src family tyrosine kinase inhibitor. It is approved at a dose of 100 mg orally daily for the treatment of chronic myeloid leukemia in chronic phase (CML‐CP). This dose schedule is associated with myelosuppression and pleural effusions. Anecdotal data suggest that lower doses may be as effective and less toxic. The aim of this study was to assess the efficacy and safety of a lower dose of dasatinib (50 mg daily) in patients with newly diagnosed CML‐CP. METHODS: Seventy‐five patients with newly diagnosed CML‐CP received dasatinib 50 mg daily. The eligibility and response criteria were standards used in previous protocols. RESULTS: At a median follow‐up of 9 months, 60 patients were evaluable for a response at 3 months. The rates of patients achieving BCR‐ABL1 transcript levels ≤ 10% and ≤ 1% at 3 months by the International Standard were 93% and 72%, respectively. The rates of complete cytogenetic response by conventional cytogenetics or fluorescence in situ hybridization at 6 and 12 months were 86% and 88%, respectively. At 12 months, 79%, 71%, and 46% of the patients had achieved a major molecular response, a molecular response with a 4.0‐log reduction, and a molecular response with a 4.5‐log reduction, respectively. Nine patients had a dose interruption for ≤14 days. Only 1 patient developed a pleural effusion requiring a dose reduction to 20 mg. All patients remained alive and with no transformation so far. CONCLUSION: Dasatinib 50 mg daily is active and well tolerated in patients with newly diagnosed CML‐CP. It should be further explored as a new potential standard‐of‐care option for chronic myeloid leukemia. Cancer 2018;124:2740‐2747 . © 2018 American Cancer Society Abstract : Dasatinib at a lower dose of 50 mg daily is active and well tolerated in the treatment of newly diagnosed chronic‐phase chronic myeloid leukemia. Dasatinib at a lower dose is also likely to be more cost‐effective. See also pages 2687‐9.